THE ROLE OF PARENTS IN EFFORTS TO ANTICIPATE THE NEGATIVE IMPACT OF SOCIAL MEDIA DEVELOPMENT ON ADOLESCENT BEHAVIOR IN THE X BINJAI TIMUR KOTA BINJAI - Hemawati Hemawati; Putri Sakura; Samsul Rizal (Proceeding International Seminar of Islamic Studies, 2021)
Hyperactive teens on social media who try to keep up with the times. Many parents do not care or even let their children use social media according to their children's wishes without parental supervision. Anticipating this problem, the role of parents is very important in overcoming the negative impact of social media on adolescent behavior, where parents have the task of fulfilling children's thinking with positive things that are in accordance with Islamic teachings in building good mindsets for children. Parents are also tasked with providing supervision of children's social media so that children use social media wisely. The purpose of this study was to determine the role of parents in anticipating the negative impact of social media, the negative impact of social media on adolescent behavior in the X neighborhood of Sumber Karya Village, East Binjai District, Binjai City and parents' efforts to anticipate the negative impact of social media on adolescent behavior in X Sumber Karya Village, East Binjai District, Binjai City. The research location is the X neighborhood of Sumber Karya Village, East Binjai District, Binjai City. This research includes field research (field research) with a descriptive qualitative approach. The results showed that: The role of parents in anticipating the negative impacts of social media: acting as educators, directors and supervisors. The negative impact of social media on adolescent behavior is that teenagers always want to be considered cool in social media, prefer to communicate using social media rather than communicate directly and affect adolescent health. Parents' efforts to anticipate the negative impacts of social media: always provide advice about the negative impacts of social media, provide supervision and provide limits on the use of social media Keyword: The Role Of Parents, The Negative Impact Of Social Media, Adolescent Behavior